Solve for x.

-3(-4x - 3) = -27
A. x = -3
B. x = -2
C. x = 3
D. x = 2

3 answers

We start with the equation:

\[ -3(-4x - 3) = -27 \]

First, we distribute the -3 on the left side:

\[ 12x + 9 = -27 \]

Next, we isolate the term with \(x\) by subtracting 9 from both sides:

\[ 12x = -27 - 9 \] \[ 12x = -36 \]

Now, we solve for \(x\) by dividing both sides by 12:

\[ x = \frac{-36}{12} \] \[ x = -3 \]

Thus, the solution is:

\[ \boxed{-3} \]

The correct answer is A. \(x = -3\).

are you sure this is correct

Let's double-check the steps to ensure accuracy.

Starting with the original equation:

\[ -3(-4x - 3) = -27 \]

First, distribute the \(-3\) on the left side:

\[ -3 \cdot -4x + -3 \cdot -3 = 12x + 9 \]

So, we have:

\[ 12x + 9 = -27 \]

Next, we isolate \(12x\) by subtracting \(9\) from both sides:

\[ 12x = -27 - 9 \] \[ 12x = -36 \]

Now, divide both sides by \(12\):

\[ x = \frac{-36}{12} \] \[ x = -3 \]

Yes, the calculations are correct, and the solution for \(x\) is indeed:

\[ \boxed{-3} \]

So, the answer is A. \(x = -3\). Thank you for your patience in confirming the solution!